PENGARUH KUALITAS INFORMASI EKOWISATA HUTAN MBELILING MANGGARAI BARAT TERHADAP LOYALITAS WISATAWAN - Hesti Duari, IPutu Hardani; Halouvin, Yulianus Hadianto (Sekolah Tinggi Pariwisata AMPTA, 2018)
In the world of tourism, building a quality information is one thing to note because it involves decision-making for the visitors or tourists. The quality of this information will be processed with a quality information system and then create results / output that is useful for people who need information to travel them. Today's eco-tourism has become a more dominant choice for tourists who want to visit Indonesia especially to eastern Indonesia one of them is West Mangggarai Regency. Information about the ecotourism area of Mbeliling Forest, West Manggarai regency has become the attention of the visitors because inside the mbeliling forest there are some very promising tourism potentials, it could be for the years to come, this area will often be visited by many tourists. The purpose of the study to determine whether there is a significant influence the quality of information (independent variable) to the loyalty of tourists (dependent variable). Using quantitative method, the questionnaire will be done some analysis such as data quality test (validity and reliability), simple linear regression analysis. The results showed that as much as 15.3% variable quality of information affect the loyalty of tourists among some other things that affect (84.7%). It is also explained that there is a positive effect of information quality on tourist loyalty of 0,322. Keywords: Information Quality, Ecotourism, Tourist Loyalty